Interpretasi Makna Lagu Rakyat Biak Wampasi Wambarek (Sebuah Pendekatan Hermeneutika) - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
Folksong is a part of the oral tradition. It was born from the people cultures. Wampasi Wambarek is a folksong from Biak’s people. It consists of eight lyrics. This research tells about Wampasi Wambarek folksong. This research discusses about its meaning on that folksong using the hermeneutics approach. The method of this reseach is a qualitative description. It is a library research. Its data was collected by reading teks and note recording technique. The hermeneutics approach was used by researcher’s interpretation. So it was analyzed according by the words on its folksong lyrics, the lyrics on that folksong, and the comprehensive meaning of folksong.